2009
DOI: 10.1016/j.physletb.2009.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Left–right asymmetric holographic RG flow with gravitational Chern–Simons term

Abstract: We consider the holographic renormalization group (RG) flow in three dimensional gravity with the gravitational Chern-Simons term coupled to some scalar fields. We apply the canonical approach to this higher derivative case and employ the Hamilton-Jacobi formalism to analyze the flow equations of two dimensional field theory. Especially we obtain flow equations of Weyl and gravitational anomalies, and derive c-functions for left and right moving modes. Both of them are monotonically non-increasing along the fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
3
8
0
Order By: Relevance
“…In our opinion, this approach carries some ambiguities since there is no robust definition of such c-functions (or at least the precise interpretation of it). Our derivations and conclusions do not rely on these definitions, nevertheless we are in perfect agreement with the results reported in [20].…”
Section: Jhep11(2015)145supporting
confidence: 91%
See 1 more Smart Citation
“…In our opinion, this approach carries some ambiguities since there is no robust definition of such c-functions (or at least the precise interpretation of it). Our derivations and conclusions do not rely on these definitions, nevertheless we are in perfect agreement with the results reported in [20].…”
Section: Jhep11(2015)145supporting
confidence: 91%
“…This was the approach used in [20], and they showed that their was no radial dependence onĉ. In our opinion, this approach carries some ambiguities since there is no robust definition of such c-functions (or at least the precise interpretation of it).…”
Section: Jhep11(2015)145mentioning
confidence: 99%
“…2 In the context of topologically massive gravity of [16], holographic RG flows were studied in [17].…”
Section: Dedicated To the Loving Memory Of My Fathermentioning
confidence: 99%
“…for the recent discussions on three dimensional gravity with the gravitational Chern-Simons term 3. The equivalent expressions of c ± or the entropy in CTMG were obtained in various ways[21]-[27],[43],[37].…”
mentioning
confidence: 99%